Mental Health Literacy: Comparison between Clinical Based Setting and Academic Based Setting of Nursing Students - Yurni, Yurni; Hanurawan, Fattah; Hitipeuw, Imanuel; Murwani, Danardana; Nurhusna, Nurhusna (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Abstract Mental health literacy for nursing students is very important because they are expected to be able to cope with the physical and psychological consequences of mental illness. This study investigates the level of mental health literacy of nursing students from two different educational settings, namely educational based setting and clinical based setting. Using purposive sampling method to select participants, a cross sectional survey was collected to describe the MHL of 66 nursing students. The results of this study showed that there was no difference in the level of mental health literacy between nursing students from clinical based settings and educational based settings. Both groups had high mental health literacy. The conclusion of this study is that educational background does not affect the level of mental health literacy.